Picture and picture method media puzzle assisted on learning outcomes in the cognitive realm of Grade V elementary school students - Erdi Guna Suriani; Emi Sulistri; Nina Marsela (Universitas Ahmad Dahlan, 2022)
This study aims to describe the magnitude of the influence of the Picture and Picture model with the help of Puzzle Media on the science learning outcomes of fifth-grade students. The instruments in this study were student learning outcomes question sheets and student learning activity observer sheets. The instrument in this study was the student learning outcomes question sheets and student learning activity observer sheets. The type of research used is quantitative research with the quality experiment method. The population in this study were all fifth-grade students of SDN 06 Sungai Rusa, totalling 48 students. Samples were taken using the saturated sample technique. The sample that became the experimental class was the VA class using the Picture and Picture model with the help of Puzzle media, while the VB class was the control class using the conventional method. The data analysis technique in this study used the T-test and the Effect Size test. The results of the hypothesis test show that the value of tcount 3.365 and value ttable 2.012 for a 5 percent and dk 48, which means that there is a significant effect on learning outcomes between students who applied the Picture and Picture learning model assisted by Puzzle media and students who received direct learning. So it can be concluded that the use of the Picture and Picture model with the help of Puzzle media can affect student learning outcomes